2014
DOI: 10.1016/j.sbspro.2014.02.063
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Technical Oral Presentation: Voices of the Stakeholder

Abstract: In Universiti Teknologi Malaysia, engineering students are expected to deliver technical oral presentations on numerous occasions prior to graduation. These presentations include survey report presentations, laboratory report presentations, project/assignment presentations as well as final year project presentations. Technical presentation refers to a prepared formal presentation on scientific, engineering, technological, business types, regulatory, legal, managerial or social scientific information topics to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 3 publications
0
14
0
2
Order By: Relevance
“…The findings from this study were used to help establish guidelines to help instructors teach the academic skills for oral presentations. Bankowski ( 2010) noted that students had difficulty selecting appropriate topics, and similar problems with this form of focused, academic thinking were observed by C. W. Y. Chen (2011), Honga and Fong (2012), Stapa et al (2014), and L. Lee (2014), highlighting the need for more training in tailoring suitable discussion topics and developing analytical thinking. However, Chou (2011) found that individual presentation work helped students link and organize information for a topic, a skill that was lacking from group work.…”
Section: Table 3 (Continued)mentioning
confidence: 85%
See 3 more Smart Citations
“…The findings from this study were used to help establish guidelines to help instructors teach the academic skills for oral presentations. Bankowski ( 2010) noted that students had difficulty selecting appropriate topics, and similar problems with this form of focused, academic thinking were observed by C. W. Y. Chen (2011), Honga and Fong (2012), Stapa et al (2014), and L. Lee (2014), highlighting the need for more training in tailoring suitable discussion topics and developing analytical thinking. However, Chou (2011) found that individual presentation work helped students link and organize information for a topic, a skill that was lacking from group work.…”
Section: Table 3 (Continued)mentioning
confidence: 85%
“…For example, one group of Malaysian students were unfamiliar with the requirements for an academic presentation, and they were also unaware of the type of questions a review panel would ask, adding to their anxiety, which was already high as they were presenting in their second language (Radzuan & Kaur, 2011). A similar situation was observed in dissertation proposals (Honga & Fong, 2012), and Stapa et al (2014) found a lack of knowledge of presentations skills and requirements during a presentation was a major causes of student anxiety. Hsu et al (2008), Sun (2009, and Huang and Hung (2010) found that when introducing LT for language learning, specific guidelines on how the LT can assist language learners are needed or the learners will question the use of the technology and abandon the learning task before it is completed.…”
Section: The Need For Specific Guidelinesmentioning
confidence: 98%
See 2 more Smart Citations
“…The importance of oral communication skills has been identified in numerous research studies (Ab.Rahim, 2008;Adzmi, Bidin, & Ibrahim, 2009;Al-Tamimi & Shuib, 2010;Bhattacharyya, 2014;Chia-Jung, 1991;Chia, Johnson, Chia, & Olive, 1999;Kaewpet, 2009a;Kakepoto, Omar, Boon, & Iqbal, 2012;Mohamed et al, 2014;Moslehifar & Ibrahim, 2012;Radzuan & Kaur, 2011;Stapa, Murad, & Ahmad, 2014;Talif & Noor, 2009;Zaid & Kamarudin, 2011). If engineers work in a situation where English is a medium of communication, they are expected to use English both formally and informally.…”
Section: Oral Communication Skills In Englishmentioning
confidence: 99%